(untitled) (Research, Society and Development, 2020)
Due to the importance of dairy activity in the municipalities of the state of Rondônia, the objective was to characterize milk production in the properties of the municipality of Nova Brasilândia D’Oeste - RO. The methodology was composed by the application of a questionnaire containing questions related to the production chain, using a sample of dairy farmers distributed through the municipality’s vicinal lines. The analysis was performed with the aid of Microsoft Office Excel spreadsheets®. The results obtained show a low technological level in dairy activity in the municipality, with an average daily production of 4.73 L per cow. The animals are kept in pastures of tropical grasses, in which the genus Brachiaria stands out, present in 100% of the properties. The supply of bulky and concentrated source for supplementation of animals is not significant, causing seasonality in dairy production in dry periods because it does not meet the nutritional requirements of the herd. In relation to herd health, producers carry out mandatory vaccines of foot-and-mouth disease and brucellosis. Milking hygiene deserves attention for the low level of use of hygiene techniques such as pre- and post-dipping and diagnostic tests and mastitis control. Manual milking is performed in 92% of the evaluated properties. The low productivity of the municipality is related to non-specialized animals, the low technological level employed in the properties and the low adoption of technical assistance by producers. The data obtained were important to know and characterize the profile of dairy properties in this region and visualize the need for investment of the activity.